1999
DOI: 10.1037/h0089012
|View full text |Cite
|
Sign up to set email alerts
|

An examination of racial/ethnic and gender bias on curriculum-based measurement of reading.

Abstract: A study examined racial/ethnic and gender bias on curriculum-based measurement (CBM) of reading with African-American and Caucasian male and female regular education students across grades 2-5. Simultaneous multiple regression analyses were conducted by grade to examine group differences on CBM as an estimate of reading comprehension. Regression equations were estimated with CBM, gender, race/ethnicity, and the interactions of gender and race/ethnicity with CBM. Results indicated that CBM is a biased indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 19 publications
(32 reference statements)
2
38
1
1
Order By: Relevance
“…The test has a speed component built in; children have 1 min to read and make as many word selections as they can in each text (Fuchs, Fuchs, & Compton, 2004). There is evidence that student performance on CBM-Maze test is related to accurate and efficient word reading (Deno, Maruyama, Espin, & Cohen, 1989;Fuchs et al, 2001;Hosp & Fuchs, 2005;Kranzler, Miller, & Jordan, 1999;Paris, Carpenter, Paris, & Hamilton, 2005;Stahl & Hiebert, 2006) and to skills that support the construction of a mental representation of the text such as vocabulary and inference making (Tolar et al, 2011).…”
Section: Selection Of Reading Comprehension Tests and Processing Demandsmentioning
confidence: 98%
“…The test has a speed component built in; children have 1 min to read and make as many word selections as they can in each text (Fuchs, Fuchs, & Compton, 2004). There is evidence that student performance on CBM-Maze test is related to accurate and efficient word reading (Deno, Maruyama, Espin, & Cohen, 1989;Fuchs et al, 2001;Hosp & Fuchs, 2005;Kranzler, Miller, & Jordan, 1999;Paris, Carpenter, Paris, & Hamilton, 2005;Stahl & Hiebert, 2006) and to skills that support the construction of a mental representation of the text such as vocabulary and inference making (Tolar et al, 2011).…”
Section: Selection Of Reading Comprehension Tests and Processing Demandsmentioning
confidence: 98%
“…However, more recent studies have brought the universality of this finding into question. Kranzler, Miller, and Jordan (1999) conducted a study with 326 students in grades 2-5. They concluded that ''at Grades 4 and 5, CBM performance overestimates the reading comprehension of African American students and underestimates that of Caucasians'' (Kranzler et al,p.…”
Section: Level Of Challengementioning
confidence: 99%
“…It is troubling to speculate that the Grade 6 students might not have expended sufficient effort to perform well on the tests. On the other hand, this apprehension may be entirely unwarranted in that it is possible to speculate on several other reasons why the differences between grades might have occurred: (a) the participants were entirely different as individuals; (b) perhaps, as a group, Grade 6 students presented with language capabilities that did not sustain the ability to perform well, as the larger study (Gordon Pershey, 2003, 2008 suggested; (c) the two forms of the state-mandated tests used in each of the grades could have been dissimilar in difficulty, with the sixth-grade test presenting inordinate difficulty or the fourth-grade test being less demanding; (d) the Grade 6 participants may not have been prepared by the curriculum and instruction offered in the fifth and sixth grades to take the sixth-grade test; (e) the normed and criterionreferenced instruments used may have been unrepresentative of the capabilities of these students (Kranzler & Miller, 1999;Washington, 1996). Nevertheless, regardless of the applicability of these reasons, tests usually seek to establish Downloaded by [University of Chicago Library] at 15:55 04 November 2014 that age and ability are covarying gradients.…”
Section: Discussionmentioning
confidence: 97%